2009
DOI: 10.1128/jb.01654-08
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystallographic and Mutational Studies of Fluoroacetate Dehalogenase from Burkholderia sp. Strain FA1

Abstract: Fluoroacetate dehalogenase catalyzes the hydrolytic defluorination of fluoroacetate to produce glycolate. The enzyme is unique in that it catalyzes the cleavage of a carbon-fluorine bond of an aliphatic compound: the bond energy of the carbon-fluorine bond is among the highest found in natural products. The enzyme also acts on chloroacetate, although much less efficiently. We here determined the X-ray crystal structure of the enzyme from Burkholderia sp. strain FA1 as the first experimentally determined three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…The dimerization interface encompasses an average surface area of 1,365 Å 2 on each monomer. Dimerization is a feature commonly seen in the crystal structures of bacterial ␣/␤ hydrolases (29,43,57).…”
Section: Vol 192 2010 Structure Of An Epoxide Hydrolase Virulence Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimerization interface encompasses an average surface area of 1,365 Å 2 on each monomer. Dimerization is a feature commonly seen in the crystal structures of bacterial ␣/␤ hydrolases (29,43,57).…”
Section: Vol 192 2010 Structure Of An Epoxide Hydrolase Virulence Fmentioning
confidence: 99%
“…While confirming the predicted similarity between ArEH and Cif, our distance matrix alignment also revealed that the most closely related known structure was actually that of the fluoroacetate dehalogenase from Burkholderia sp. strain FA1 (FAc-DEX FA1), with a Z score of 35.7 and an rmsd of 1.9 Å. FAc-DEX FA1 is an ␣/␤ hydrolase that defluorinates fluoroacetate to form glycolic acid (29), thus detoxifying this compound, which can form a potent aconitase inhibitor if ingested (24). As a family, the HADs are closely related in sequence to the EHs and also utilize an aspartic acid side chain for initial nucleophilic attack (52).…”
Section: Vol 192 2010 Structure Of An Epoxide Hydrolase Virulence Fmentioning
confidence: 99%
“…46) The following mutant enzymes showed no activity toward fluoroacetate and chloroacetate: F34A, D104A, R105A, R108A, D128A, Y147A, H149A, W179A, Y212A, H271A, and F272A. In contrast, replacement of Trp150 with Ala did not significantly affect the activity toward chloroacetate, whereas that toward fluoroacetate was completely lost due to this mutation.…”
Section: )mentioning
confidence: 86%
“…40) Mutation of Asp104 and His271 of FAc-DEX FA1 resulted in a total loss of the enzyme activity, suggesting that the reaction mechanism is conserved between these enzymes. 46) To investigate the reaction mechanism of fluoroacetate dehalogenase further, the crystal structure of FAc-DEX FA1 was determined. 46) This enzyme belongs to the / hydrolase superfamily and shares three-dimensional structural similarity with epoxide hydrolase and haloalkane dehalogenase.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation